Новые тенденции в междунaродной aкaдемической мобильности (Вестник КазНУ. Серия Востоковедения, 2018)
International student mobility is becoming an increasingly common phenomenon in higher educationin many countries of the world. The purpose of this article is to study current trends in the fieldof academic mobility in the world. In the course of the work, we studied the articles and reports of anumber of international educational organizations. The dominant trend of the past few years has beenthe growing flow of students from developing countries to universities in Europe, primarily British ones,and the United States. However, the number of countries competing for the placement of foreign students is growing everyyear, but the increase in the number of students leaving for study abroad in the next decade will significantlyslow down. The decline in growth rates is due not only to the deterioration of the political climatein the United States and European countries but also to a large extent to the increase of local investmentsin higher education in many countries. Many potential students now want to study in their home countries,and the greatest decline in absolute terms is expected to be in South Korea and Malaysia.